Validity of a self-administered food frequency questionnaire in the estimation of heterocyclic aromatic amines - Iwasaki, Motoki; Mukai, Tomomi; Takachi, Ribeka; Ishihara, Junko; Totsuka, Yukari; Tsugane, Shoichiro (Cancer causes & control, 2014)
Background: Clarification of the putative etiologic role of heterocyclic aromatic amines (HAAs) in the development of cancer requires a validated assessment tool for dietary HAAs. This study primarily aimed to evaluate the validity of a food frequency questionnaire (FFQ) in estimating HAA intake, using 2-amino- 1 -methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) level in human hair as the reference method. Methods: We first updated analytical methods of PhIP using liquid chromatography-electrospray ionization/tandem mass spectrometry (LC-ESI/MS/MS) and measured 44 fur samples from nine rats from a feeding study as partverification of the quantitative performance of LC-ESI/MS/MS. We next measured PhIP level in human hair samples from a validation study of the FFQ (n = 65). HAA intake from the FFQ was estimated using information on intake from six fish items and seven meat items and data on HAA content in each food item. Correlation coefficients between PhIP level in human hair and HAA intake from the FFQ were calculated. Results: The animal feeding study of PhIP found a significant dose–response relationship between dosage and PhIP in rat fur. Mean level was 53.8 pg/g hair among subjects with values over the limit of detection (LOD) (n = 57). We found significant positive correlation coefficients between PhIP in human hair and HAA intake from the FFQ, with Spearman rank correlation coefficients of 0.35 for all subjects, 0.21 for subjects with over LOD values, and 0.34 for subjects with over limit of quantification. Conclusion: Findings from the validation study suggest that the FFQ is reasonably valid for the assessment of HAA intake.